2020
DOI: 10.3928/1081597x-20200710-01
|View full text |Cite
|
Sign up to set email alerts
|

Optical Performance of a Monofocal Intraocular Lens Designed to Extend Depth of Focus

Abstract: To test the performance of a new monofocal intraocular lens, intended to extend depth of focus (Tecnis® Eyhance, ICB00) (ICB-IOL), in comparison to a timetested standard monofocal IOL (Tecnis® 1-piece, ZCB00) (ZCB-IOL) of same platform and material. MethodsAssessment of the optical performance of the two IOLs was made in-vitro using an optical test bench with a model eye. The spherical aberration (SA), modulation transfer function (MTF) and the area under the MTF (MTFa) were obtained for pupil sizes ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 38 publications
9
65
2
1
Order By: Relevance
“…The optical quality measured using the OQAS in our study was comparable between the two groups, based on the OSI, MTF cutoff, and Strehl ratio, consistent with previous reports [3]. However, few studies have analyzed the optical quality in pseudophakic eyes using the OQAS and the contributions of the material and design features of IOLs have not yet been fully characterized [11,15,16]. Higher OSI values have been observed in multifocal IOLs, with mean OSIs of 1.45 in eyes implanted with the ZCB00 and a mean of 2.50 in eyes implanted with the ZMB00 (Advanced Medical Optics, Santa Ana, CA, USA), a multifocal IOL made of hydrophobic acrylic material [11].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The optical quality measured using the OQAS in our study was comparable between the two groups, based on the OSI, MTF cutoff, and Strehl ratio, consistent with previous reports [3]. However, few studies have analyzed the optical quality in pseudophakic eyes using the OQAS and the contributions of the material and design features of IOLs have not yet been fully characterized [11,15,16]. Higher OSI values have been observed in multifocal IOLs, with mean OSIs of 1.45 in eyes implanted with the ZCB00 and a mean of 2.50 in eyes implanted with the ZMB00 (Advanced Medical Optics, Santa Ana, CA, USA), a multifocal IOL made of hydrophobic acrylic material [11].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a significant correlation was observed between OSI values and glare in the multifocal group, indicating that the OSI may be a reliable index for the visual quality of multifocal IOLs. The OQAS values for the ZCB00 and ICB00 did not differ significantly, indicating similar optical qualities between the two IOLs [3,11,16].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The unique anterior surface lies on the center deviation of the Eyhance ICB00 IOL may explain those results [ 24 ]. Previous study showed that the through-focus MTF curve of the ICB00 shifted to a myopic defocus of − 0.50 D at a 2.0 mm pupil size and the maximum MTF value was obtained at − 0.5 D defocus [ 25 ]. However, in this study, the maximum MTF value was obtained at 0.0 D defocus without myopic shift of the MTF curve at a 2.0 mm pupil size.…”
Section: Discussionmentioning
confidence: 99%